Hubungan Budaya Organisasi dengan Kinerja Karyawan di Bank Syariah Indonesia Cabang Bogor - Ria Kusumaningrum; Farah Chalida Hanoum; Indyah Winasih (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Organizational culture is a set of assumptions or belief systems, values, and norms developed within the organization that are used as guidelines for employees to act in overcoming various problems and become a differentiator between one organization and another. Every company will certainly expect a good performance from each of its employees as a benchmark for the achievements obtained. A good organizational culture will certainly bring the company to the expected conditions. This study aims to determine the close relationship between organizational culture and the performance of employees of Bank Syariah Indonesia Bogor branch by using survey methods, interviews and questionnaires to 65 respondents. The data analysis method used is the product moment correlation coefficient and the coefficient of determination. Based on the results of research using the product moment correlation coefficient, the result is rs = 0.822, meaning that organizational culture with the performance of employees of Bank Syariah Indonesia Bogor branch has a very strong relationship, the coefficient of determination on organizational culture is 67.56% which shows the magnitude of the contribution of variables organizational culture on employee performance variables. While the remaining 32.44% is influenced by other factors that are not measured. The results of hypothesis testing are obtained tcount > ttable with a value of 11,456 > 1.6694 then accept Ha reject Ho, meaning that there is a real relationship between organizational culture (X) and employee performance (Y) at Bank Syariah Indonesia Bogor branch Keyword: culture organization, employee performance.